Co-infections of Schistosoma spp. and Malaria with Hepatitis Viruses from Endemic Countries: A Systematic Review and Meta-Analysis - Taghipour, Ali; Bahadory, Saeed; Olfatifar, Meysam; Norouzi, Mojtaba; Majidiani, Hamidreza; Foroutan, Masoud (Infectious Disorders - Drug Targets, 2022)
Background: Co-infection of schistosomiasis and malaria with hepatitis B virus (HBV) and hepatitis C virus (HCV) are common in countries where schistosomiasis and malaria are endemic. Objective: The present systematic review and meta-analysis was conducted to assess the prevalence of malaria/hepatitis viruses and Schistosoma/hepatitis viruses’ co-infections. Materials and Methods: Relevant published studies on the co-infection of malaria and Schistosoma spp. with HBV and HCV were retrieved via international databases (PubMed, Scopus, Web of Science, and Google Scholar). Regarding meta-analysis, the random128;effect model was employed by forest plot with a 95% of confidence interval (CI). Results: A total of 22 studies, including 15 studies with malaria/hepatitis viruses’ co-infection and 7 studies with Schistosoma/hepatitis viruses’ co-infection met the eligibility criteria. The co-infection of malaria/HCV and malaria/HBV in different populations were 15% (95% CI, 0-77%) and 5% (95% CI, 1-10%), respectively. Moreover, Schistosoma/HCV and Schistosoma/HBV co infection were detected in 7% (95% CI, 0-54%) and 2% (95% CI, 0-7%), respectively. Conclusion: The overlaps between Schistosoma spp. and malaria with hepatitis B and C viruses in endemic countries with lower income levels were high, which deserve further attention.
Keywords: subtropical areas